Unobserved heterogeneity and the relation between earnings and firm size: evidence from two developing countries - Söderbom, M; Teal, F; Wambugu, A (Elsevier, 2005)
Large firms in Ghana and Kenya pay much higher wages than small ones. We use panel data to show this is not the result of employing high-ability individuals. The size effect remains substantial with controls for individual fixed effects.